Upaya Guru BK dalam Mengembangkan Adversity Quotient Pada Siswa SMAN 1 Manyak Payed - Muliani Muliani; Mawardi Siregar; Rizky Andana Pohan (Prodi Bimbingan dan Konseling Islam, 2020)
This study aims to describe the adversity quotient of SMAN 1 Manyak Paid students and the efforts of the BK teacher in developing adversity quotient in students. The research method used in this study is a qualitative type with a descriptive approach. Data were collected using observation, interview, and documentation techniques. The determination of research subjects or informants in this study was done by purposive sampling. Data were analyzed using the Miles and Huberman technique. The results showed that (1) the description of adversity quotient in SMAN 1 Manyak Paid students can be seen from all four dimensions, namely a) Dimension of control, students cannot control themselves when facing a problem. b) The dimension of ownership (recognition), students can admit mistakes made by apologizing and promising not to repeat the same mistakes again. c) The reach dimension (achievement), some students have the ability to limit difficulties so that they do not enter into other lives and some students have not been able to limit it. d) The dimension of endurance students assumes every problem they face requires a long time in solving it. (2) the efforts of BK teachers in developing adversity quotient in SMAN 1 Manyak Payed students in the form of classical guidance and individual counseling services, where classical guidance is used first if there is no change, then individual counseling and forms of collaboration between BK teachers and teachers will be conducted Students and parents to support the process of solving students' difficulties